Biological landscape and nanostructural view in development and reversal of oxaliplatin resistance in colorectal cancer - Mehrdad Hashemi; Nastaran Esbati; Mohsen Rashidi; Sadaf Gholami; Rasoul Raesi; Seyed Shahabadin Bidoki; Mohammad Ali Sheikh Beig Goharrizi; Yasamin Sadat Mousavi Motlagh; Ramin Khorrami; Alireza Tavakolpournegari; Noushin Nabavi; Rongjun Zou; et al. (Translational Oncology, 2024)
The treatment of cancer patients has been mainly followed using chemotherapy and it is a gold standard in improving prognosis and survival rate of patients. Oxaliplatin (OXA) is a third-platinum anti-cancer agent that reduces DNA synthesis in cancer cells to interfere with their growth and cell cycle progression. In spite of promising results of using OXA in cancer chemotherapy, the process of drug resistance has made some challenges. OXA is commonly applied in treatment of colorectal cancer (CRC) as a malignancy of gastrointestinal tract and when CRC cells increase their proliferation and metastasis, they can obtain resistance to OXA chemotherapy. A number of molecular factors such as CHK2, SIRT1, c-Myc, LATS2 and FOXC1 have been considered as regulators of OXA response in CRC cells. The non-coding RNAs are able to function as master regulator of other molecular pathways in modulating OXA resistance. There is a close association between molecular mechanisms such as apoptosis, autophagy, glycolysis and EMT with OXA resistance, so that apoptosis inhibition, pro-survival autophagy induction and stimulation of EMT and glycolysis can induce OXA resistance in CRC cells. A number of anti-tumor compounds including astragaloside IV, resveratrol and nobiletin are able to enhance OXA sensitivity in CRC cells. Nanoparticles for increasing potential of OXA in CRC suppression and reversing OXA resistance have been employed in cancer chemotherapy. These subjects are covered in this review article to shed light on molecular factors resulting in OXA resistance.